Intersubjectivity and the disconnection in Patricia Lockwood’s No One Is Talking About This (2021) - Marling, Raili (Critical psychology (Lawrence & Wishart), 2024)
Intersubjectivity has long fascinated thinkers who have challenged the notion of the unitary subject. Its alternative, the intersubjective self, is permeable and reciprocal, open to and shaped by the others. Questions of intersubjectivity have become increasingly urgent as a result of the rise of social media which metaphorically brings users together as a shared mind. This article probes questions of relationality and the narratable nature of human self (cf Cavarero in Relating Narratives: Storytelling and Selfhood. Routledge , London, 2000; Butler in Giving an Account of Oneself Fordham. University Press, New York, 2005) in a work of fiction that compares the relationalities created by social media and the subjective experience: Patricia Lockwood’s novel, No One Is Talking About This (2021). The very opacity of the novel probes the question of what (inter)subjectivity might mean in the age of social media. More broadly, the article seeks to test the relevance of feminist theories of relational and narrative self within the context of the novel.